2022
DOI: 10.1021/acs.jcim.1c01523
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Delta Variant Decreases Nanobody Binding and ACE2 Blocking Effectivity

Abstract: The Delta variant spreads more rapidly than previous variants of SARS-CoV-2. This variant comprises several mutations on the receptor-binding domain (RBD Delta ) of its spike glycoprotein, which binds to the peptidase domain (PD) of angiotensin-converting enzyme 2 (ACE2) receptors in host cells. The RBD–PD interaction has been targeted by antibodies and nanobodies to prevent viral infection, but their effectiveness against the Delta variant remains unclear. Here, we investigated RBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
3
4
0
Order By: Relevance
“…Comparisons of the binding affinities for the VOCs with other theoretical studies were reported by us in previous work . For example, Golcuk and coauthors recently also showed that the RBD-ACE2 binding affinity is strengthened for the Delta in comparison with the wt as seen by us. In their work, they identified an additional contribution from increased hydrophobic interactions .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Comparisons of the binding affinities for the VOCs with other theoretical studies were reported by us in previous work . For example, Golcuk and coauthors recently also showed that the RBD-ACE2 binding affinity is strengthened for the Delta in comparison with the wt as seen by us. In their work, they identified an additional contribution from increased hydrophobic interactions .…”
Section: Resultssupporting
confidence: 77%
“…For example, Golcuk and coauthors recently also showed that the RBD-ACE2 binding affinity is strengthened for the Delta in comparison with the wt as seen by us. In their work, they identified an additional contribution from increased hydrophobic interactions . Other results that became available after this comparison also report the same trends. , For the recent variants from the Omicron family, no data is yet available at the moment of writing this work.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…As revealed in Fig. 2c, the key residues of the RBD in Model 1 are Q498, Q493, N501, F486, Y505, F456, G496, and L455, which match the key residues of the RBD of the RBD-ACE2 complex reported in previous studies, 24,[45][46][47] suggesting that our model is reliable. The detailed binding mode diagrams are shown in Fig.…”
Section: Resultssupporting
confidence: 84%
“…Although previous studies of molecular dynamics simulations have been conducted to investigate delta variants in presence of nanobodies [23] or to evidence that omicron variant binds more strongly to human cells than the wild type, [24,25] our study is limited to the published data in the Protein Data Bank without any ligand. We have explored the mobility and flexibility changes in twelve spike proteins.…”
Section: Introductionmentioning
confidence: 99%